The Bibliometric Analysis of Public-Private Partnership in the Field of Education - Septariani, Sella Fadia; Yuliana, Lia (JURNAL AL-TANZIM, 2025)
This study explores the evolving role of Public-Private Partnerships (PPP) in the education sector, with a focus on their impact on infrastructure development and educational practices. The research aims to identify key trends in PPP-related education research from 2000 to 2023, shedding light on the shift from infrastructure-focused projects to more innovative approaches involving pedagogy, digital inclusion, and educational policy. Previous studies have primarily concentrated on infrastructure development and the financial implications of PPP, while the effects on educational quality and technology integration remain underexplored. This study employs bibliometric analysis using data from the Publish or Perish software to analyze academic articles, citation patterns, and key thematic trends within the field of PPP in education. Findings reveal a significant shift towards discussions on pedagogical innovation, digital inclusion, and the alignment of PPP projects with educational policy. The research emphasizes the growing role of PPP in transforming educational environments through strategic collaboration. These findings provide valuable insights into how future PPP can better support equitable and effective education systems, with implications for policymakers, educators, and stakeholders in education reform.